The 18-O Chilean Uprising and the Making of Transnational Political identies - Messineo, Francesca (PARTECIPAZIONE E CONFLITTO, 2022)
This work focuses on the Chilean uprising of October 2019, and briefly characterizes its events. However, the core interest is to observe and question the international impact and everyday transnational features of this movement. Drawing on G. Schiller's thoughts and combining them with transnational social movements' scholarship, the analysis develops around two key axes. On the one hand, it charts mainly indirect diffusion through the spread of ideas and practices that travelled from Chile (and from Latin America) and grew to become embedded in social movements worldwide. On the other hand, it offers an ethnographic account of the transnational networks that have mobilized in support of this struggle in Italy, with particular attention paid to Chileans abroad. In this way, our work highlights the parallel movement from everyday transnational experiences to the formation of transnational political identities, and from shared political identities to transnational daily interactions. By exploring the interplay between different diffusion mechanisms, this case study contributes to the discussion of the role of political agency in shaping diffusion dynamics, and offers new insights into the construction of transnational collective identities.